Factors affecting hemodialysis adequacy in patients undergoing hemodialysis: a cross-sectional study - Wayunah Wayunah; Muhammad Saefulloh; Yanganto Yanganto (Universitas Aisyah Pringsewu, 2023)
Hemodialysis is the most preferred renal replacement therapy for patients with chronic kidney failure worldwide. The indicator of the success of hemodialysis therapy is the fulfillment of the adequacy of the hemodialysis dose as measured by Kt/V. Many factors affect the adequacy of hemodialysis, including internal factors and external factors of the patient. This study aimed to analyze the factors that affect the adequacy of hemodialysis in patients undergoing hemodialysis at Indramayu Hospital. Research design using a cross-sectional approach. The sample in this study was 44 respondents who were taken based on purposive sampling. The result showed that the average Kt/V was 1.71 with the lowest Kt/V value being 0.76 and the highest Kt/V being 2.33. Of 44 respondents, 24 (54.5 %) found adequacy achieved, and 20 (45.5 %) respondents did not achieve adequacy. Factors related to hemodialysis adequacy are gender (p=0.000; OR=4.0), dry weight (p=0.006; OR=7.286), dialyzer reuse (p=0.005; OR=8.000), and quick of blood (p=0.38; OR=4.5). Suggestions for hemodialysis nurses to be able to evaluate, especially the use of dialyzer reuse no more than 4 times, and maintain a quick blood speed of at least 250 ml/minute to achieve adequacy. Abstrak: Hemodialisa merupakan terapi pengganti ginjal yang paling banyak dipilih untuk penderita gagal ginjal kronik di seluruh dunia. Indikator keberhasilan terapi hemodialisa adalah terpenuhinya kecukupan dosis hemodialisa yang diukur dengan Kt/V. Ada banyak faktor yang mempengaruhi adekuasi hemodialisa, diantaranya faktor internal dan factor eksternal pasien. Tujuan penelitian ini adalah untuk menganalisis factor-faktor yang mempengaruhi adekuasi hemodialisa pada pasien yang menjalani hemodialisa di RSUD Indramayu. Desain penelitian menggunakan pendekatan cross-seksional. Sampel dalam penelitian ini berjumlah 44 responden yang dipilih berdasarkan purposive sampling. Hasil penelitian diketahui rata-rata Kt/V adalah 1,71 dengan nilai Kt/V terendah adalah 0,76 dan Kt/V tertinggi adalah 2,33. Dari 44 responden ditemukan sebanyak 24 (54,5 %) responden adekuasi tercapai, dan 20 (45,5 %) responden adekuasi tidak tercapai. Faktor yang berhubungan dengan adekuasi hemodialisa adalah faktor jenis kelamin (p=0,000; OR 4,0), berat badan kering (p=0.006; OR 7.286), dialyzer reuse (p=0.005; OR=8.000), dan quick of blood (p=0.38; OR=4.5). saran ditujukan untuk perawat hemodialisa agar dapat melakukan evaluasi terutama penggunaan dializer reuse tidak lebih dari 4 kali, serta mempertahankan kecepatan quick of blood minimal 250 ml/menit agar adekuasi tercapai